Pengembangan Booklet Keanekaragaman Kupu-Kupu Di Kabupaten Kerinci dan Sekitarnya Sebagai Sumber Belajar Pada Materi Animalia Kelas X SMA: (Booklet Development of Butterfly Biodiversity in Kerinci Regency and its Surroundings as Learning Resource in Chapter Animalia Class X Senior High School) - Bestia Dewi; Afreni Hamidah; Tedjo Sukmono (BIODIK, 2020)
Learning resources play an important role in the learning process. The benefits of learning resources are as a support for learning activities, adding and expanding the presentation of material that might not be summarized in the textbooks. Most of the learning resources used by students today are still in unattractive form. The available learning resources also do not explain examples of animals that can be found around (contextual). Also, the difficulty of getting learning resources for Animalia materials that are per the learning objectives is an obstacle that causes the unavailability of Animalia learning resources. Therefore, innovation is needed to develop a learning resource that is suitable for the learning objectives. This development was done due to a lack of learning resources with the elaboration of animals found in surrounding (Contextual). This development study aimed to design a booklet of butterfly biodiversity in Kerinci regency and its surroundings as a learning resource in Chapter Animalia Class X Senior High School, to determine teachers' and students' responses. The development model used in this study was the ADDIE model. ADDIE model consists of 5 steps: Analysis, Design, Development, Implementation, and Evaluation. The booklet was validated by media experts and material experts in the very appropriate category. The response from the teachers to the booklet was good. The response from the students to the booklet in a small group trial and large group trials was very good. Based on the results of the study it can be concluded that booklet of butterfly biodiversity in Kerinci regency and its surroundings is appropriate for use by high school grade X students as learning resources for Animalia chapter.  Abstrak. Sumber belajar berperan penting dalam kegiatan pembelajaran. Beberapa manfaat sumber belajar yaitu sebagai penunjang kegiatan pembelajaran, menambah dan memperluas sajian materi yang mungkin tidak terangkum didalam buku paket. Sebagian besar sumber belajar yang digunakan siswa saat ini masih dalam bentuk yang kurang menarik. Sumber belajar yang tersedia juga tidak menjelaskan contoh-contoh hewan yang dapat ditemui disekitar (kontekstual). Selain itu, sulitnya mendapatkan sumber belajar materi Animalia yang sesuai dengan tujuan pembelajaran menjadi kendala yang menyebabkan tidak tersedianya sumber belajar materi Animalia di sekolah. Sehingga, diperlukan suatu inovasi untuk mengembangkan suatu sumber belajar yang sesuai dengan tujuan pembelajaran. Tujuan dari penelitian pengembangan ini adalah untuk menghasilkan  booklet keanekaragaman kupu-kupu di Kabupaten Kerinci dan sekitarnya sebagai sumber belajar pada materi Animalia kelas X SMA, mengetahui respon guru dan respon siswa terhadap booklet yang dikembangkan. Model pengembangan yang digunakan dalam penelitian ini adalah model ADDIE. Model ADDIE terdiri dari 5 tahapan yaitu Analysis, Design, Development, Implementation dan Evaluation. Booklet divalidasi oleh ahli media dan ahli materi dengan perolehan hasil sangat layak. Respon guru terhadap booklet pada kategori baik. Respon siswa terhadap booklet pada ujicoba kelompok kecil dan kelompok besar pada kategori sangat baik. Berdasarkan hasil penelitian dapat disimpulkan bahwa booklet keanekaragaman kupu-kupu di Kabupaten Kerinci dan sekitarnya layak digunakan siswa kelas X SMA sebagai sumber belajar materi Animalia.